2020
DOI: 10.3390/cancers12123583
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-MICA/B Antibody and IL-15 Rescue Altered NKG2D-Dependent NK Cell Responses in Hepatocellular Carcinoma

Abstract: Natural killer (NK) cells play a pivotal role in cancer immune surveillance, and activating the receptor/ligand interaction may contribute to control the development and evolution of hepatocellular carcinoma (HCC). We investigated the role of the natural killer group 2 member D (NKG2D) activating receptor and its ligand, the major histocompatibility complex class I chain-related protein A and B (MICA/B) in patients with cirrhosis and HCC subjected to surgical resection, patients with cirrhosis and no HCC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Zhou et al 53 observed lower proportions of cytotoxic T cells, NK cells and increased regulatory T cells by immunohistochemistry in iCCA tumors. Notably, reduced frequencies of NKG2D+ NK cells have been observed by our group in HCC 27 and by others in non-hepatic tumors. 32 , 58 Here we showed that NKG2D activating receptor expression was indeed reduced in PBMC and tumor-infiltrating NK cells making them potentially unsuitable for optimal engagement of MICA/B proteins expressed on tumor cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Zhou et al 53 observed lower proportions of cytotoxic T cells, NK cells and increased regulatory T cells by immunohistochemistry in iCCA tumors. Notably, reduced frequencies of NKG2D+ NK cells have been observed by our group in HCC 27 and by others in non-hepatic tumors. 32 , 58 Here we showed that NKG2D activating receptor expression was indeed reduced in PBMC and tumor-infiltrating NK cells making them potentially unsuitable for optimal engagement of MICA/B proteins expressed on tumor cells.…”
Section: Discussionsupporting
confidence: 76%
“…Since the release of MICA/B proteins by tumor cells and the concomitant increase of their soluble form are thought to represent a mechanism of immune escape evading NK immune surveillance in several neoplastic settings 38 , 39 including HCC, 27 , 40 we measured serum MICA in iCCA patients. As shown in Figure 2a , sMICA was higher in iCCA patients compared with HC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, lower baseline levels of CD16 correlate with decreased ADCC responses in NK cells: compared with NK cells obtained from healthy donors, it was demonstrated that NK cells from cancer patients showed a significant reduction of both direct killing and ADCC against tumors, which was due to CD16 down-regulation [ 58 ]. In cancer patients, the expression levels of CD16, DNAM-1, and NKG2D have also been reported down-regulation on NK cells [ 59 , 60 ]. A Western blot assay using NK cells after stimulation with tumor cells may further add proof to possible CD16 shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, 7C6 acts synergistically with the HDACi panobinostat through stabilizing tumor cell surface MICA/B expression ( 224 ) and exhibits synergy with human cytokine-induced NK cells (CIK) in vitro ( 225 ). A different humanized anti-MICA/B mAb stimulates NK cell-mediated cytotoxicity in vitro against primary hepatocellular carcinoma cells ( 226 ). In addition, three novel mAb (5E10, 7G10 and 6E1) that recognize the α3 domain of MICA interfere with the immunosuppressive activity of sMICA on human NK cells and stimulate their activation in an Fc-dependent manner due to the formation of immune complexes with sMICA ( 119 ).…”
Section: The Opportunity For the Nkg2d-nkg2dl Axis In Immuno-oncologymentioning
confidence: 99%